QUALIFIED PRACTICE PERIOD IN PREPARING FUTURE SPECIAL TEACHERS FOR PROFESSIONAL ACTIVITY (American Journal of Pedagogical and Educational Research, 2023)
In this article discusses about qualified practice period in preparing future special teachers for professional activity.